2008
DOI: 10.1021/jm070543k
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Undesirable hERG Potency of Chemokine Receptor Antagonists Using Baseline Lipophilicity Relationships

Abstract: The inhibition of the hERG channel by noncardiovascular drugs is a side effect that severely impedes the development of new medications. To increase hERG selectivity of preclinical compounds, we recommend the study of nondesolvation related interactions with the intended target and hERG using a baseline lipophilicity relationship approach. While this approach is conventionally used in studies of potency, we demonstrate here that it can help in selectivity issues. Studies of hERG selectivity in four in-house cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 87 publications
3
47
0
Order By: Relevance
“…Medicinal chemistry experience shows that the addition of a single methyl group to the structure of a lead compound can change binding affinity by one order of magnitude [38][41]. Classically, this paradigm is associated with the small molecule part of a binding interaction as the ligand is amenable to chemical modification.…”
Section: Resultsmentioning
confidence: 99%
“…Medicinal chemistry experience shows that the addition of a single methyl group to the structure of a lead compound can change binding affinity by one order of magnitude [38][41]. Classically, this paradigm is associated with the small molecule part of a binding interaction as the ligand is amenable to chemical modification.…”
Section: Resultsmentioning
confidence: 99%
“…Sudden cardiac death arising from an arrhythmia (Torsade de Pointes) is a known issue in drug development because a large number of drugs with features of lipophilic amines show unintended inhibition of the human ether-à-go-go related gene (hERG), which encodes a potassium ion channel protein [120]. Because small molecule CKR antagonists often contain a basic amine in order to interact with a glutamic acid residue present in the seventh transmembrane domain of CKRs, this structural feature may also lead to non-selective inhibition of hERG, thus increasing the risk of arrhythmia in a small group of patients.…”
Section: Ckr Antagonist Selectivitymentioning
confidence: 99%
“…Reproduced with permission from Rockefeller Press [43]. vanced strategies to measure and avoid nonhydrophobic interactions of CKR antagonists with the hERG channel can help select agents with decreased risk of cardiac complications [120,121]. Fig.…”
Section: Ckr Antagonist Selectivitymentioning
confidence: 99%
“…If such a reduction is not possible, or is accomplished but hERG activity still remains, they caution that specific structural modification is necessary. Shamovsky et al [94] demonstrated the use of lipophilicity-adjusted hERG potency to reduce hERG liability in a chemokine receptor antagonist project.…”
Section: Qsar Modelsmentioning
confidence: 99%